Cystic fluid chromogranin A levels in different pancreatic cystic lesions - Oruç, Nevin; Aydın, Ahmet; Barutcuoğlu, Burcu; Aktan, Çağdaş; Nart, Deniz; Veral, Ali (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Pancreatic cystic lesions have a broad spectrum of differential diagnosis. There is an ongoing demand to identify specific and sensitive cystic fluid markers for the differential diagnosis of pancreatic cysts. We aimed to evaluate the diagnostic value of cystic fluid chromogranin A (CgA) in the differential diagnosis of pancreatic cysts. Materials and Methods: Patients who underwent endoscopic ultrasound (EUS)-guided aspiration for pancreatic cysts were included in the study. Cytopathological analysis and biochemical analysis, including cystic fluid carcinoembryonic antigen (CEA), amylase, Ca 19-9, and CgA, were performed. Results: Fifty-three patients were included in the study. The final diagnosis of patients was 14 pancreatic pseudocysts, 10 intraductal papillary mucinous neoplasms (IPMNs), 8 mucinous cystic neoplasms (MCN), 8 serous cystadenomas (SCAs), 2 cystic pancreatic neuroendocrine tumors (PNETs), and 11 others. The mean CgA levels were 50.51±130.04 ng/mL in pseudocysts, 12.38±8.59 in MCN, and 13.76±10.90 in cystic PNET. There was only one patient with a very high cystic fluid CgA (515.49 ng/mL) and was diagnosed as pseudocyst developed in chronic pancreatitis patient. Two patients with cystic PNET had normal levels of cystic fluid CgA. Conclusion: Cystic fluid CgA is not a useful marker for the differential diagnosis of cystic PNETs. It also has no value in the differential diagnosis of other pancreatic cysts.